The hope and hype of ellagic acid and urolithins as ligands of SARS-CoV-2 Nsp5 and inhibitors of viral replication - Elisa Bianconi; Anna Gidari; Maria Souma; Samuele Sabbatini; Deborah Grifagni; Carlo Bigiotti; Elisabetta Schiaroli; Lucia Comez; Alessandro Paciaroni; Francesca Cantini; Daniela Francisci; Antonio Macchiarulo (Taylor & Francis Group, 2023)
Non-structural protein 5 (Nsp5) is a cysteine protease that plays a key role in SARS-CoV-2 replication, suppressing host protein synthesis and promoting immune evasion. The investigation of natural products as a potential strategy for Nsp5 inhibition is gaining attention as a means of developing antiviral agents. In this work, we have investigated the physicochemical properties and structure-activity relationships of ellagic acid and its gut metabolites, urolithins A-D, as ligands of Nsp5. Results allow us to identify urolithin D as promising ligand of Nsp5, with a dissociation constant in the nanomolar range of potency. Although urolithin D is able to bind to the catalytic cleft of Nsp5, the appraisal of its viral replication inhibition against SARS-CoV-2 in Vero E6 assay highlights a lack of activity. While these results are discussed in the framework of the available literature reporting conflicting data on polyphenol antiviral activity, they provide new clues for natural products as potential viral protease inhibitors.